Temperature evolution analysis of AZ31B magnesium alloy during quasi-static fracture. Issue 12 (12th August 2016) - Zhang, H. X.; Wang, Z. N.; Zhou, Y. G.; Guo, S. F.; Yan, Z. F.; Wang, W. X.
Abstract : Fracture toughness of AZ31B magnesium alloy subjected to quasi-static loading was investigated by infrared thermography. The results showed that temperature evolution around the crack propagation path during fracture underwent three stages: initial steady stage, monotonic increase stage and final steady stage. The temperature increase at the beginning of stage II is nearly corresponding to the initiation of unstable crack propagation. And based on this phenomenon, a method applying infrared thermography to estimate fracture toughness of AZ31B magnesium alloy was proposed. Fracture toughness was calculated through infrared thermography, which was in good agreement with the result determined by traditional standard method. Finally, the fracture mechanism was investigated.